Self Management in the Perspective of Islamic Education: A Study of Behavioral Psychology and Modern Sufism - Supeno; Diana Elfiyatul Afifah (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study aims to analyze the concept of self-management in the perspective of Islamic education by reviewing its integration with behavioral psychology theory and modern Sufi values. Through library research, this study explores classical Islamic works and relevant contemporary theories to find common ground between spiritual disciplines and modern psychology. The results of the study show that self-management in Islam is rooted in the values of tazkiyatun nafs, murāqabah, and muhāsabah, which function as internal mechanisms for behavioral control. Meanwhile, behavioral psychology explains self-management as a process of strengthening self-control and forming positive habits through reinforcement. The integration of the two gives rise to the behavioral-spiritual education paradigm, which is an educational model that balances spiritual, emotional, and behavioral awareness. This study contributes to broadening the understanding of Islamic education to be more responsive to modern challenges, especially in character building and mental health of students in the global era.